KAJIAN MUTASI GEN PADA DNA MITOKONDRIA (MTDNA) SEBAGAI PREDISPOSISI DIABETES MELITUS - Yuliana, Dewi (Fakultas Farmasi UMI, 2012)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated levels of blood glucose are associated with abnormalities in the metabolism of carbohydrates, fats, and proteins. Diabetes mellitus type 2 (DM type 2) is one of chronic diseases that occur with increasing number of patients. The involvement of genetic and environment factors, it make genetic studies of this disease becomes very important. One form of type 2 diabetes is Maternal Inherited Diabetes and Deafness (MIDD) is caused by a mutation of mitochondrial DNA(mtDNA).Keywords : Mutasi, DNA mitokondria (mtDNA), diabetes mellitus